Дослідження на багатошаровому поселенні Байківці VІ у Тернопільській обл. - Дерех, О.М. (Археологічні дослідження в Україні, 2010)
Results of rescue archaeological research at Baykivtsi VI multilayer settlement (the Early Iron Age and the Ancient Rus period) in Ternopil Region are presented.